2001
DOI: 10.1002/1616-5195(20011001)1:7<275::aid-mabi275>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Investigation of Poly[(R)-3-hydroxybutyrate] Lamellar Single Crystals: Relationship between Molecular Weight and Enzymatic Degradation Behavior

Abstract: Enzymatic degradation behavior of a lamella of single crystals of poly(R)‐3‐hydroxybutyrate (P(3HB)) with an extracellular polyhydroxybutyrate (PHB) depolymerase purified from Alcaligenes faecalis T1 has been investigated by atomic force microscopy (AFM) in order to obtain further information for the chain packing state of P(3HB) in a lamellar single crystal. Two kinds of P(3HB) single crystals with different molecular weights, denoted respectively as H‐ and L‐P(3HB) for high and low molecular weights, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…It seems likely that the parallel arrays are the polymer itself that is being imaged. PHAs form a well‐known lamellar spherulitic microstructure [23–25] and we have observed a structure similar to these parallel arrays in spun‐cast thin films of PHB‐ co ‐V [26]. We further suggest that globular structures traversing the surface of the parallel arrays are the protein machinery that mediates structure, synthesis, and depolymerization.…”
Section: Discussionmentioning
confidence: 60%
“…It seems likely that the parallel arrays are the polymer itself that is being imaged. PHAs form a well‐known lamellar spherulitic microstructure [23–25] and we have observed a structure similar to these parallel arrays in spun‐cast thin films of PHB‐ co ‐V [26]. We further suggest that globular structures traversing the surface of the parallel arrays are the protein machinery that mediates structure, synthesis, and depolymerization.…”
Section: Discussionmentioning
confidence: 60%
“…Murase et al30,31 studied the enzymatic degradation behavior of P[( R )‐3HB] single crystals fixed on highly ordered pyrolytic graphite (HOPG), and reported that PHB single crystals were preferentially degraded through the formation of some cracks and crevices along the crystallographic a ‐ and b ‐axes, respectively. Lee et al29 have reported on the melting behavior and enzymatic degradation of P[( R )‐3HB] single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…To study the enzymatic degradation of the crystalline region of PHA, a number of studies using single crystals of P[( R )‐3HB] and its copolymers have been performed 22–31. It has been reported that the enzymatic degradation by the extracellular PHB depolymerase takes place at the edges and the ends of single crystals to yield a splintered morphology along the crystallographic a ‐axis rather than at their chain‐folding surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymatic degradation and adsorption on P(3HB) single crystals by extracellular PHB depolymerases has been reported by Hocking et al,14 Nobes et al,15 Iwata et al16,17 and Murase et al18,19 The partially degraded crystalline lamellae were splintered along the long axes of the crystals, despite the fact that there was no decrease in molecular weight. From these observations, an edge‐attack model for the degradation of P(3HB) single crystals was proposed 15.…”
Section: Introductionmentioning
confidence: 78%